Evaluation of Iron Deficiency Anemia Frequency as a Risk Factor in Glaucoma - Penpe Gul Firat; Ersan Ersin Demirel; Seyhan Dikci; Irfan Kuku; Oguzhan Genc (Anemia)
Purpose. Iron deficiency anemia is an important public health problem. Also it is considered to be a risk factor for many diseases. The study demonstrates the iron deficiency anemia frequency in glaucoma patients and compares with the normal subjects. We aimed to determine the iron deficiency anemia frequency in glaucoma patients. Methods. Prospective, controlled study in a single university hospital setting. A total of 130 normal subjects (Group 1) and 131 glaucoma patients (Group 2) were included. The erythrocytes parameters, hemoglobin, red blood cell, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin concentration, mean corpuscular hemoglobin, and red blood cell distribution width, and iron status indicators, Fe (iron), total iron binding capacity, and ferritin of the cases, in normal subjects and glaucoma patients were compared. Results. There was no statistically significant difference for the erythrocyte parameters between the groups (p≥0.05). The number of the patients with iron deficiency anemia in both groups was similar. No statistically significant difference was found in the comparison of erythrocyte parameters and iron status indicators values according to the number of antiglaucomatous agents and visual field changes according to the presence of anemia in Group 2 (p≥0.05). A statistically significant difference was found only in MCH when the erythrocyte parameters and iron status indicators values of the cases in glaucoma patients were compared with the glaucoma duration (p<0.05). Conclusion. The iron deficiency anemia frequency was like the normal population in glaucoma patients.